Molecular identification of Mymarothecium viatorum and Anacanthorus penilabiatus in extensive native fish farming systems of the Peruvian Amazon - Cabrera-Soregui, Milagros; Torres-Lozano, Karel; Garcia-Candela, Enrique; Mesias-Valle, Fernando; Martinez-Rojas, Rosa; Cruz-Neyra, Lidia; Mondragón-Martínez, Aarón; Ebert, Mariana Bertholdi [UNESP]; da Silva, Reinaldo José [UNESP]; Cala-Delgado, Daniel Leonardo (Elsevier, 2024)
Piaractus brachypomus (Pacú) is the main native fish species cultivated in Peru and holds great potential for growth in aquaculture from the Peruvian Amazon. Between October 2021 and January 2022 in two fish producing farms in the Amazon region of San Martín in Peru, P. brachypomus individuals were examined for parasite evaluation. A total of 6366 monogeneans were isolated from the gills of 30 fish, revealing a prevalence of 100%, with an abundance and mean intensity of 212 parasites per fish. Monogeneans were morphologically identified as Mymarothecium viatorum and Anacanthorus penilabiatus. The genetic divergence in the 28S rDNA gene found among A. penilabiatus sequences was 0.1% and among Anacanthorus spp. it ranged from 0.9% to 7.5%. The genetic divergence found among the M. viatorum sequences was 0.3%. These finding represents the first molecular data of M. viatorum and A. penilabiatus in Peru using the 28S rDNA gene of these monogeneans. The new sequences obtained will contribute to future studies on the phylogenetic relationships among dactylogyrids. However, further research with a broader range of host-parasite samples and additional genetic markers is needed to clarify these relationships and provide stronger support for the phylogenetic positions.
Keywords: 28S rDNA; Anacanthorus; Dactylogyridae; Mymarothecium; Peruvian Amazon